Systematic engineering of Pichia pastoris for high-level production of recombinant human granulocyte-macrophage colony-stimulating factor - Zhenzhen Cheng; Keyu Gong; Yuchao Song; Zhenchang Guo; Wenjun Guan (Bioresource Technology, 2026)

Bacteria-inspired mechano-chemical nanovaccines enable multi-activation of dendritic cells for potent antitumor immunity - Hongjuan Zhao; Chenxi Zhao; Yuting Cang; Jinpei Sun; Qing Li; Keyu Zong; Yajing Wang; Di Meng; Qingling Song; Lei Wang (Chemical Engineering Journal, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Larix gmelinii growth limitation shifts from nitrogen availability to drought under warming and permafrost degradation - Zecheng Chen; Binqing Zhao; Wenqi Song; Hans W. Linderholm; Jan Altman; Keyu Zhang; Hanjun Dong; Xinran Huang; Haoyuan Chen; Xiaochun Wang (Global and Planetary Change, 2026)

Establishing tracer gas dilution as a potential reference method for in-stack CO2 emission metrology - Yayong Liu; Zhe Bi; Xiaoping Song; Chi Tu; Keyu Chen; Shao-Meng Li (Journal of Cleaner Production, 2026)

Alkali–organic synergy rewires microbial acid tolerance to restore nitrogen cycling in acidic soils - Mengke Li; Keyu Yao; Jean Damascene Harindintwali; Min Qian; Nan Wu; Yanwei Kan; Ziyi Song; Xian Xiao; Peng Liu; Yuan Zhao (Journal of Environmental Management, 2026)

Comprehensive chemical molecular characterization of petroleum-contaminated soils: Unraveling physical migration and biotransformation processes in the vadose and saturated zones - Wang Yu; Yuruo Wan; Jiuhao Song; Keyu Duan; Junjie Guan; Qi Gao; Yuping Zhang; Jianhui Ma; Jie Ma (Environmental Pollution, 2026)

Fingerprinting complex mixed oil spills at refineries: Source identification, quantitative source apportionment, and biodegradation assessment - Wang Yu; Jiayi An; Jiuhao Song; Junjie Guan; Keyu Duan; Wei Zhou; Liting Tian; Jie Ma (Water Research, 2025)

A temporal correlation topology graph model based on mode-intrinsic and mode-specific characterization using differentiated decoupling module with distribution independence constraints for multimode adaptive process monitoring - Keyu Yao; Hongbo Shi; Bing Song; Yang Tao (Process Safety and Environmental Protection, 2025)

Impact of landform on Spatial-Temporal distribution and Scenario-Based prediction of carbon stocks in arid Regions: A Case study of Xinjiang - Keyu Song; Weiming Cheng; Baixue Wang; Hua Xu (CATENA, 2025)

Three birds with one stone: Constructing Janus multilayer carbon fabric to boost solar-driven interfacial evaporation, electrical power generation and inhibit VOCs volatilization - Keyu Ding; Yaqin Yang; Yanan Mao; Dongdong Tong; Shizhou Lu; Bo Song (Chemical Engineering Journal, 2024)

Fluid tracing and evolution at micron-scale of shales in faulted lake basin: Evidence and constraints from in-situ analysis of analcime - Junran Wang; Chao Liang; Yingchang Cao; Shunyao Song; Keyu Liu; Shengyu Yang; Jinqiang Tian; Danish Khan; Bixiao Xin (Marine and Petroleum Geology, 2024)

Occurrence of ochratoxin A in Sichuan bacon from different geographical regions and characterization and biocontrol of ochratoxigenic Aspergillus westerdijkiae strain 21G2-1A - Kaidi Hu; Keyu Guo; Xingjie Wang; Song Wang; Jianlong Li; Qin Li; Ning Zhao; Aiping Liu; Li He; Xinjie Hu; Yong Yang; Likou Zou; et al. (Food Research International, 2024)

Rapid and convenient synthesis of “green” ammonium-modified chitosan composite sponge with the existence of ascorbic acid for highly efficient removal of Congo red (CR) - Keyu Ren; Yanan Fan; Guozheng Xing; Mengge Zhai; Jie Sheng; Yishan Song (Carbohydrate Polymers, 2024)

Towards Realizing Intelligent Coordinated Controllers for Multi-USV Systems Using Abstract Training Environments - Sulemana Nantogma; Keyu Pan; Weilong Song; Renwei Luo; Yang Xu (Journal of Marine Science and Engineering, 2021)
Unmanned autonomous vehicles for various civilian and military applications have become a particularly interesting research area. Despite their many potential applications, a related technological challenge is realizing realistic coordinated autonomous control and decision making in complex and multi-agent environments. Machine learning approaches have been largely employed in simplified simulations to acquire intelligent control systems in multi-agent settings. However, the complexity of the physical environment, unrealistic assumptions, and lack of abstract physical environments derail the process of transition from simulation to real systems. This work presents a modular framework for automated data acquisition, training, and the evaluation of multiple unmanned surface vehicles controllers that facilitate prior knowledge integration and human-guided learning in a closed-loop. To realize this, we first present a digital maritime environment of multiple unmanned surface vehicles that abstracts the real-world dynamics in our application domain. Then, a behavior-driven artificial immune-inspired fuzzy classifier systems approach that is capable of optimizing agents’ behaviors and action selection in a multi-agent environment is presented. Evaluation scenarios of different combat missions are presented to demonstrate the performance of the system. Simulation results show that the resulting controllers can achieved an average wining rate between 52% and 98% in all test cases, indicating the effectiveness of the proposed approach and its feasibility in realizing adaptive controllers for efficient multiple unmanned systems’ cooperative decision making. We believe that this system can facilitate the simulation, data acquisition, training, and evaluation of practical cooperative unmanned vehicles’ controllers in a closed-loop.

Development of a compact continuum tubular robotic system for nasopharyngeal biopsy - Liao Wu; Shuang Song; Keyu Wu; Chwee Ming Lim; Hongliang Ren (Medical & Biological Engineering & Computing, 2017)

Production of marker-free transgenic rice expressing tissue-specific Bt gene - Chengxiang Qiu; Jatinder Singh Sangha; Fengshun Song; Zhiyun Zhou; Ao Yin; Keyu Gu; Dongsheng Tian; Jianbo Yang; Zhongchao Yin (Plant Cell Reports, 2010)